Engines datasets - Namoano, Bernadin; Starr, Andrew; Emmanouilidis, Christos; Ruiz Carcel, Cristobal (Cranfield University, 2020)
Data represents urban DMU trains engines condition monitoring data.
Keywords: 'Diesel multiple unit'; 'exhaust'; 'engine speeds'; 'Automotive Engineering Materials'; 'Rail Transportation and Freight Services'; 'Transport Engineering'; 'Computer Engineering'